1015 Sleep Duration and Physical and Mental Health Among Adult Survivors of Childhood Cancer: Results from the St. Jude Lifetime Cohort. (27th May 2020) - Lubas, M M; Mandrell, B N; Ehrhardt, M J; Ness, K K; Srivastava, D; Robison, L L; Hudson, M M; Krull, K R; Brinkman, T M
Abstract: Introduction: Sleep disturbances are prevalent among adult survivors of childhood cancer, though little is known about associations between sleep and health in this vulnerable population. Methods: Survivors recruited from the St. Jude Lifetime Cohort (n=911; 52% female; mean age 34 years; 26 years post-diagnosis) completed surveys assessing habitual sleep patterns and mental health and underwent comprehensive physical examinations. A subset of survivors (n=491) completed sleep actigraphy. Short sleep duration was defined as sleeping <7 hours per night, assessed via self-report or actigraphy. Clinically-assessed health outcomes were defined as grade ≥2 using modified CTCAE criteria for cardiac, pulmonary, and renal conditions. Anxiety and depression were defined as scores ≥90 th percentile on the Brief Symptom Inventory-18. Covariates included childhood cancer treatment exposures, demographics, body mass index, and physical inactivity. Separate logistic or modified Poisson (common outcomes) regression models were computed for each health category to estimate odds ratios (OR) or relative risks (RR) and 95% confidence intervals (CI). Results: Self-report and actigraphy-assessed short sleep was identified in 44% and 42% of survivors, respectively. However, these measures were weakly correlated (r=0.23). In adjusted multivariable models, self-reported short sleep was associated with higher risk of pulmonary conditions (RR=1.3, 95% CI=1.1-1.7), depression (OR=2.6, 95% CI=1.4-5.1) and anxiety (OR=3.4, 95% CI=1.6-6.8), while associations with cardiac (RR=1.10, 95% CI=0.94-1.30) and renal conditions (OR=1.30, 95% CI=0.79-2.13) were not significant. There were no significant associations between actigraphy-assessed short sleep and any of the health outcomes. Conclusion: Habitual self-reported short sleep was associated with clinically ascertained adverse health outcomes. Although the temporality of these associations cannot be determined in this cross-sectional study, sleep is a modifiable health behavior and improving sleep may improve health in survivors. Measures of self-reported sleep may have unique value when assessing the relationship between sleep and health. Support: CA225590, K. Krull Principal Investigator; CA195547, M. Hudson and L. Robison Principal Investigators; CA21765, C. Roberts, Principal Investigator